2015
DOI: 10.1002/ejsp.2116
|View full text |Cite
|
Sign up to set email alerts
|

When immigrant groups “misbehave”: The influence of perceived deviant behavior on increased threat and discriminatory intentions and the moderating role of right‐wing authoritarianism

Abstract: In two studies, we tested the relationship between non-immigrant individuals' perceptions of deviant behavior carried out by Muslims and foreigners and discriminatory intentions towards these outgroups. Based on a longitudinal and a representative cross-sectional sample, we showed that two different types of perceived deviant behavior (Study 1, Muslims' unwillingness to integrate; and Study 2, foreigners' hostility towards the non-immigrant majority group) are related to increased intergroup threat, which in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 50 publications
(75 reference statements)
0
30
0
2
Order By: Relevance
“…About SDO, we found that Islamoprejudice totally mediates the relation between this social variable and the perception of terrorist threat for the country. Unlike authoritarian people (Kauff et al, ), individuals with high levels of SDO have not generally an increased sensitivity for threatening issues. However, their negative attitudes and cognitions about the Islamic world could have influenced their perceived social threat from terrorism, perhaps facilitating the association of Muslim individuals with that of terrorists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About SDO, we found that Islamoprejudice totally mediates the relation between this social variable and the perception of terrorist threat for the country. Unlike authoritarian people (Kauff et al, ), individuals with high levels of SDO have not generally an increased sensitivity for threatening issues. However, their negative attitudes and cognitions about the Islamic world could have influenced their perceived social threat from terrorism, perhaps facilitating the association of Muslim individuals with that of terrorists.…”
Section: Discussionmentioning
confidence: 99%
“…Crowson (2009) found that RWA was a strong predictor of the perceived threat from terrorists whereas SDO completely failed to predict it. Furthermore, recent research found that RWA influenced perceived threat because people with higher levels of RWA are more sensitive to any source of threat (Cohrs & Ibler, 2009;Kauff, Asbrock, Issmer, Thörner, & Wagner, 2015). Conversely, people with high levels of SDO see the world as a competitive place, but not as dangerous, although they have been found to feel endangered by outgroups that were seen as direct competitors and with conflicting goals (Thomsen, Green, & Sidanius, 2008).…”
Section: Perceived Threat From Islamic Terrorismmentioning
confidence: 99%
“…In addition to realistic and symbolic threats, the intergroup threat theory (ITT) has been complemented with elements of group esteem threats, being personally threatened in intergroup interactions and having negative expectations concerning the out-group, for example (Brown, 2010;Koomen, W. & Van der Pligt, 2016;Stephan & Stephan, 2000). Indeed, perceived group threats have been reported to predict out-group discrimination in various studies (Kauff et al, 2015;Riek, Mania, & Gaertner, 2006;Wirtz, van der Pligt & Doosje, 2016).…”
Section: Online Hate and Group Relationsmentioning
confidence: 99%
“…Very few studies connected the two bodies of literature and tested the primacy of a sense of insecurity; and even fewer studies found empirical support for this claim (Cohrs & Ibler, 2009; Kauff, Asbrock, Issmer, Thörner, & Wagner, 2015; Radkiewicz, 2016). The insecurity narrative can be tested as a mediation model where a sense of insecurity holds the key to the relationship between RWA and intolerance.…”
Section: Introductionmentioning
confidence: 99%